Computational study of an air ventilation system based on CFD simulation in hospital operation theatre environment - Faraj, Muneerah ABS (2019)
In health-care facilities, pharmaceuticals, medical device production, laboratories, semiconductor production and the aerospace clean-room technology is widely implemented. The utility of the clean room allows for a range of benefits. The application is capable of reducing infection rates in health-care facilities. Hospital Operation Theatre (OT) are clean rooms which are equipped with sophisticated Heat Ventilation and Air Conditioning (HVAC) systems. HVAC system is functioned to provide Laminar Air Flow (LAF) for optimum cooling inside the OT, provide adequate number of Air Changes per Hour (ACH) and remove the air borne contamination from the surgical site. The main aim of the current work is to effectively test a HVAC system, which can provide adequate cooling with LAF and remove the contamination at the surgical site successfully. To archive the main aim, the CFD study need to validate with previous experimental work. Then parametric study need to be conduct to determine the optimal inlet and outlet configuration inside the OT. Next, the effect of heat load on the optimum airflow configuration need to be investigate using CFD software. Finally, the contamination particles need to be injected inside the optimum airflow configuration and track their movement. The parametric studies have considered various inlet and outlets along with the variation of their positions, thus effectively considering all the scenarios of Horizontal and Vertical LAF. From the result it can be concluded that vertical flow has superior efficiency compare to horizontal flow. Furthermore, the vertical flow has significant impact on the heat distribution inside the OT. Meanwhile, the horizontal flow has minimal impact on the heat distribution. Finally, the GENTRA accurately modeled the skin particles size density at various locations. The removal of the contaminants effectively from the OT shows the selected LAF for the OT works effectively in cooling the OT as well removes contamination. Increasing the contaminant particle size and density by two and three times also didn’t affect the contamination removal, thus the inlet velocity and positive pressure in the OT was enough to carry the contaminants through the outlet vents.